Gender differences in severity of desaturation events following hypopnea and obstructive apnea events in adults during sleep. (26th July 2017) - Kulkas, Antti; Duce, Brett; Leppänen, Timo; Hukins, Craig; Töyräs, Juha
Abstract: Objective : Severity estimation of obstructive sleep apnea (OSA) is currently based on the apnea–hypopnea index (AHI), which ignores individual breathing cessation event characteristics. Gender differences in the relationship between the breathing cessation event duration and the related desaturation event severity could mean that the severity of OSA is different in males and females despite a similar AHI. The aim of this work was to evaluate gender differences in the severity of peripheral oxygen desaturation events following obstructive apneas or hypopneas. Approach : Type I polysomnographic recordings of 220 males and 175 females were analyzed. The obstructive apnea and hypopnea events were divided into eight different durational categories from 10 s to 45 s with 5 s interval and >45 s. The desaturation event severities following obstructive apneas or hypopneas were compared between genders within these durational categories. Main results : Desaturations following obstructive apneas with a duration of 30–45 s were substantially more severe ( p < 0.05) in females compared to males. In contrast, areas of desaturations following hypopneas (with related hypopnea event durations ⩽30 s) were smaller ( p < 0.05) in females compared to males. In general, desaturation events following obstructive apneas were more severe compared to desaturations following hypopneas and the increase in the duration of obstructive apnea and hypopnea events led to an increase in the related desaturation severity in both genders. Significance : We found gender differences in the desaturation event severities following obstructive apneas and hypopneas. The results indicate that in females longer obstructive apneas (>30 s) could be more detrimental compared to those of males. As severe health consequences are related to the desaturation severity these aspects should be considered when estimating the severity of OSA.